2011
DOI: 10.1038/ismej.2011.22
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition in sediments resists perturbation by nutrient enrichment

Abstract: Functional redundancy in bacterial communities is expected to allow microbial assemblages to survive perturbation by allowing continuity in function despite compositional changes in communities. Recent evidence suggests, however, that microbial communities change both composition and function as a result of disturbance. We present evidence for a third response: resistance. We examined microbial community response to perturbation caused by nutrient enrichment in salt marsh sediments using deep pyrosequencing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 37 publications
12
101
3
Order By: Relevance
“…Importantly, nifH expression was detected in all gut regions and the FG, MG and PHG not only contained transcripts of N 2 -fixing bacteria related to P. propionicigenes but also groups of aerobic N 2 -fixing bacteria. This co-occurrence of aerobic and anaerobic N-fixers is likely related to presence of microaerophilic regions throughout the beetle gut and indicates some degree of functional redundancy in N 2 fixation (Bowen et al, 2011). As discussed earlier, no spirochete-related nifH transcripts were detected; this observation is likely not related to primer bias, as the same nifH primers were used to identify N 2 -fixing spirochetes in termites (Reid and Lloyd-Jones, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…Importantly, nifH expression was detected in all gut regions and the FG, MG and PHG not only contained transcripts of N 2 -fixing bacteria related to P. propionicigenes but also groups of aerobic N 2 -fixing bacteria. This co-occurrence of aerobic and anaerobic N-fixers is likely related to presence of microaerophilic regions throughout the beetle gut and indicates some degree of functional redundancy in N 2 fixation (Bowen et al, 2011). As discussed earlier, no spirochete-related nifH transcripts were detected; this observation is likely not related to primer bias, as the same nifH primers were used to identify N 2 -fixing spirochetes in termites (Reid and Lloyd-Jones, 2009).…”
Section: Discussionmentioning
confidence: 85%
“…Few studies have examined the response of microbial communities to nitrate inputs. However, distinctly different results about microbial community responses to elevated nitrate were observed, with some reporting significant changes in the microbial community (Carrino-Kyker et al, 2013) and others showing no effect (Bowen et al, 2011;Carrino-Kyker et al, 2012). The complexity of N cycling and methodologies used for these studies could be one of major reasons for this disparity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, spatial heterogeneity in production could explain the differences in the mean rates. But given the otherwise similar hydrographic and characteristics and microbial community composition of the tidal creeks (Deegan et al 2007, Bowen et al 2011) and assumptions related to nutrients and benthic chlorophyll above, it is possible that the increased photosynthetic production of oxygen was the result of the nutrient enrichment experiment.…”
Section: Nutrient Amendedmentioning
confidence: 99%
“…While marsh platform processes can drive the observations of the TIDE experiment, it is perhaps surprising that NCP in the nutrient amended tidal creek is not clearly altered by the exposure and oxidation of buried organic matter from collapsing creek banks. Results of investigations on the creeks' microbial communities may help explain this discrepancy: Bowen et al (2011) found that microbial community composition resisted change during long-term nutrient amendment (though the active community may be changing; Kearns et al 2016), and in addition to the estimated change in seasonal GPP, bacterial production increased by a similar proportion in the same creek environments and was most likely supported by labile carbon from the benthic microalgae (Bowen et al 2009). Close coupling of carbon fluxes between benthic microalgae and the bacterial community was similarly reported by Spivak and Ossolinski (2016).…”
Section: Relevance To Tide Studymentioning
confidence: 99%